Growing up trans in Canada, Switzerland, England, and Australia: access to and impacts of gender-affirming medical care. Issue 1 (2nd January 2023) - Pullen Sansfaçon, Annie; Medico, Denise; Riggs, Damien; Carlile, Anna; Suerich-Gulick, Frank
Abstract: Trans and non-binary youth (TNBY) face high levels of interpersonal and social adversity as well as disproportionate rates of mental health issues such as depression, self-harm and suicidal ideation. Among protective factors, context plays a key role. In addition to parental support, access to gender-affirming medical care begins to emerge as crucial for young people needed them. This paper compares, through thematic analysis, the experiences of TNBY with regard to access and experiences to care in Canada, Switzerland, England, and Australia. It identifies similarities and differences in barriers to access to care, as well as impacts of gender affirming care on young people and their well-being. The article concludes with a discussion on the importance of prompt and easier access to gender-affirming medical care, of training of professionals, and a hypothesis about the role of context in TNBY well-being.